Final taus and initial state polarization signatures from effective interactions of Majorana neutrinos at future e + e - colliders - Duarte, Lucía (2019)
We study the possibility of future e + e - colliders to disentangle different new physics contributions to the production of heavy sterile Majorana neutrinos in the lepton number violating channel e + e - → l + l + + 4 jets , with l= e, μ, τ. This is done investigating the final anti-tau polarization trails and initial beam polarization dependence of the signal on effective operators with distinct Dirac–Lorentz structure contributing to the Majorana neutrino production and decay, which parameterize new physics from a higher energy scale. We find that both analyses could well disentangle possible vectorial and scalar operators contributions.